posted by Tessa on .
Hey I am working on math homework that involves "Standard Form to Vertex Form by Averaging." My class is just starting to learn this today, but I am totally lost still on what to do. Can you please help? The formula for this is y=a(x - h)^2 + k
the h is the x-value vertex and the k is the y-value vertex.
I got the first one done and it looks like this:
y=-x^2 + 2x +3
-1(x^2 - 2x - 3)
-1(x + 1)(x - 3)
x= -1 and 3
y=-(-1)^2 + 2(-1) + 3
y=-1 + 2 + 3
h=-1 and k=4
i have alot more like this and i don't seem to remeber how to get 'h'